"Judging by the cover": A grounded theory study of bullying towards same-country and immigrant peers. (August 2018) - Mazzone, Angela; Thornberg, Robert; Stefanelli, Sara; Cadei, Livia; Caravita, Simona C.S.
Abstract: This study investigated students' perspectives about bullying towards same-country and immigrant peers. Thirty-five Italian and immigrant students (age range: 11–15) took part to the study. Participants were probed with two bullying scenarios, depicting respectively a new classmate from another Italian city and from a foreign country. A Grounded Theory approach was adopted to examine participants' perspectives about the motives for bullying. Findings showed that a process of socializing deviance is at the core of both forms of bullying. This social process refers to a series of shared beliefs within the peer group about the victim's deviant features. Three sub-categories related to both forms of bullying emerged from the core concept: (a) Rejecting the newcomer deviance, (b) Rejecting physical deviance, (c) and Rejecting personality deviance. These sub-categories were related to the sub-categories of bullying towards immigrant peers: (d) Rejecting cultural deviance, (e) and Learned racism. Findings are discussed in terms of their theoretical and practical relevance. Highlights: Adolescents' views for bullying same-country and immigrant peers were examined. Interview data were analyzed through a constructivist Grounded Theory approach. Findings showed that same-country and immigrant victims are perceived as deviant. The concept of deviance is co-constructed within different socio-cultural layers.